PEMBUATAN ALBUM WARNA DENGAN MENGGUNAKAN SENSOR WARNA JENIS TCS230 - Nenni Mona Aruan; Dwika Andjani; Egi Yuliora (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
This study used TCS 230 as color sensor to create colors’ album by identified output frequency of TCS 230 and measured RGB value for each color. TCS 230 converted light to electric signal by wave frequency. By using colored paper and facing to TCS 230, the LabVIEW presented its RGB value. From measurements taken, it appears that the sensor have been able to read the color, not just the primary colors (RGB) but also its derivatives. Sensors indicate that despite differences derived by naked eye color and RGB composition has only minor differences, the fixed sensor is capable of capturing the difference even though there are still errors. The amount of the average error for the color red and its derivatives is 28.0336%, while the average error in the measurement of derivatives and their blue color is 38.96% and the average error in blue and derivatives amounted to 32.99103%. Keywords:RGB,TCS 230, labVIEW, colors’ album.